Specification issues and the estimation of supply equation for rice in Malaysia - Baharumshah, Ahmad Zubaidi (Penerbit Universiti Kebangsaan Malaysia, 1991)
The supply model was nested in the general partial adjustment-adaptive expectation model. The results of the diagnostic tests suggest that the partial adjustment model is the preferred specification for the rice equation in Malaysia. The preferred model match with two other diagnostic tests: loglinear specification and autocorrelation. The estimates for the short-run price elasticity of supply are fairly low, 0.03 and the long-run elasticity is estimated at 0.11. The low price elasticities are generally in agreement with those reported earlier.